2008
DOI: 10.1175/2007jamc1547.1
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Flux Transfer over Bare-Soil Surfaces: Characteristics and Parameterization

Abstract: Parameterization of turbulent flux from bare-soil and undercanopy surfaces is imperative for modeling land-atmosphere interactions in arid and semiarid regions, where flux from the ground is dominant or comparable to canopy-sourced flux. This paper presents the major characteristics of turbulent flux transfers over seven bare-soil surfaces. These sites are located in arid, semiarid, and semihumid regions in Asia and represent a variety of conditions for aerodynamic roughness length (z 0m ; from Ͻ1 to 10 mm) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
236
1
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 188 publications
(273 citation statements)
references
References 44 publications
(60 reference statements)
11
236
1
7
Order By: Relevance
“….36 (Yang et al 2005) Thermal roughness length z 0h =70ν⋅u * −1 ⋅exp (−βu * 0.5 |T * | 0.25 ) β=7.2 s 0.5 m −0.5 K −0.25 (Yang et al 2008) Bare soil evaporation the model output with a sensitivity analysis (Fourier Amplitude Sensitivity Test by Cukier et al 1978). Assuming typical measurement errors for the initial parameter distribution they estimated that water temperature contributed up to 50 % of the overall error while the influence of wind velocity, air temperature and humidity are comparatively small, each contributing 10-20 % to the error.…”
Section: Application Of the Hm Model To A Shallow Lakementioning
confidence: 99%
See 1 more Smart Citation
“….36 (Yang et al 2005) Thermal roughness length z 0h =70ν⋅u * −1 ⋅exp (−βu * 0.5 |T * | 0.25 ) β=7.2 s 0.5 m −0.5 K −0.25 (Yang et al 2008) Bare soil evaporation the model output with a sensitivity analysis (Fourier Amplitude Sensitivity Test by Cukier et al 1978). Assuming typical measurement errors for the initial parameter distribution they estimated that water temperature contributed up to 50 % of the overall error while the influence of wind velocity, air temperature and humidity are comparatively small, each contributing 10-20 % to the error.…”
Section: Application Of the Hm Model To A Shallow Lakementioning
confidence: 99%
“…To account for these conditions, SEWAB has been adapted for the Tibetan Plateau by (1) a revised calculation of the soil thermal conductivity as used in Yang et al (2005), (2) a different formulation of the thermal roughness length after Yang et al (2008) and (3) by changing the parameterisation of bare soil evaporation according to Mihailović et al (1993). The formulations can be seen in Table 3.…”
Section: Adaptation Of Sewabmentioning
confidence: 99%
“…In subsequent work, it has become apparent that nighttime data yield much more scatter than daytime, as must be expected because at night both w T and |T 0 − T z | are small and their ratio is therefore poorly determined. This issue was emphasized by, e.g., Stewart et al (1994), Verhoef et al (1997), andYang et al (2008), whose experiments revealed representative values of kB −1 that differed greatly from the depictions illustrated in Fig. 1.…”
Section: Introductionmentioning
confidence: 87%
“…In comparison, the original analysis by Owen and Thomson (as mentioned above) yielded a = 0.6 and b = 0.45. Many of the alternative expressions listed by Yang et al (2008) share the assumption that b = 0.5. The black line in Fig.…”
Section: A Simple Credibility Checkmentioning
confidence: 99%
“…Thus, to date, various relationships have been proposed to relate this dissimilarity with other more readily measurable variables such as momentum roughness length, friction velocity, canopy height, and heat flux (e.g. Owen and Thomson, 1963;Garratt and Hicks, 1973;Thom, 1975;Brutsaert, 1982;Verma, 1989;Jensen and Hummelshøj, 1995;Zilitinkevich, 1995;Chen et al, 1997;Verhoef et al, 1997;Massman, 1999;Yang et al, 2008;Chen and Zhang, 2009;Hong and Kim, 2010). Some of these, and others, are subsequently abbreviated as shown in Table I.…”
Section: Introductionmentioning
confidence: 99%